Message from Editor-in-Chief Vol.1(2) - Shrestha, Surendra Man (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
It gives me great pleasure to publish the second issue (Jul-Dec, 2017) of Journal of NSPOI (JNSPOI). We intend to publish original research articles, case reports, review articles, personal communications, viewpoints, book reviews, letters to the editor and editorials with the main focus on original research articles. Our objective is to reach out to all the clinicians, who have knowledge and interest but lack time to record the interesting cases, research activities and new innovative procedures that help us in updating our knowledge and improving our treatment protocols. Our main emphasis is to promote genuine scientific papers and we extend our boundaries right from periodontal care to allied health sciences. We feel that there is a wide scope to explore in various fields of dental sciences. With these intentions, we welcome you to post comments related to the journal by sparing your valuable time and request you to send articles. Finally, I thank my editorial team, technical team, authors and well-wishers, who are promoting this journal. I specially thank the president of NSPOI, Dr. Shaili Pradhan who has trusted me and given this responsibility. With these words, I conclude with thanks to Dr. Bhageshwar Dhami, Executive Editor and Dr. Sujaya Gupta, Assistant Executive Editor for their relentless effort to publish this journal.